A Meta-Synthesis of Qualitative Studies Exploring Men's Sense of Masculinity Post–Prostate Cancer Treatment. Issue 4 (July 2018) - Alexis, Obrey; Worsley, Aaron James
Abstract : Background: There has been little psychosocial research concerning men's adaption to prostate cancer and treatment-related sexual dysfunction. Qualitative studies have explored men's sense of self after treatment, but the data have yet to be synthesized. Objective: The aim of this study was to report a meta-synthesis of qualitative studies exploring men's sense of masculinity after treatment of prostate cancer. Methods: Six databases were searched to identify relevant studies conducted and published between January 1990 and August 2016. Titles and abstracts were reviewed by 2 reviewers. Studies that met the inclusion criteria were selected and reviewed for quality. The extracted data were then synthesized. Results: A total of 14 studies met the inclusion criteria and passed the quality assessment. The meta-synthesis found that men's sense of masculinity diminished after treatment of prostate cancer. Impotence, incontinence, and physical changes caused psychological stress. Underpinning these factors were cultural influences and dominant ideals of what it means to be a man. Conclusions: Men had entrenched ideas about what manhood entailed. The review found that men's sense of masculinity was diminished posttreatment of prostate cancer. They felt that they could not exercise their manliness because of the adverse effects associated with prostate cancer treatment. Implications for Practice: More support and communication throughout the process are required to better inform patients of the outcomes of treatment. In addition, it would be beneficial to have open forums through which to encourage men to talk frankly about their masculine identities.